1976
DOI: 10.1017/s0031182000058510
|View full text |Cite
|
Sign up to set email alerts
|

The tegument ofSchistosoma mansoni: a histochemical investigation

Abstract: The main components of the schistosome tegument were found to be neutral glycoprotein and phospholipid; a small quantity of glycolipid was observed in the male dorsal tegument. The tegument can be differentiated from other schistosome tissues on the basis of enzyme content; three hydrolytic enzymes were shown to be specifically localized in the tegument: alkaline phosphatase, adenosine triphosphatase and indoxyl esterase. It is suggested that these enzymes could be used as intrinsic markers for tegument struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…However, this is not the case with alkaline phosphatase and ATPase. Furthermore, since the alkaline phosphatase appears to be restricted to the tegument (Cesari 1974, Wheater & Wilson 1976, the similar enrichment of this enzyme and the ATPase suggests that there is indeed little contamination of the isolated tegumental membranes with plasma membranes from other sources. Electron microscopical examination of the membrane fractions revealed a few large membranous sheets and numerous vesicles and membranous whorls (Figure 2)(c.f.…”
Section: Butterworth Et Almentioning
confidence: 94%
See 1 more Smart Citation
“…However, this is not the case with alkaline phosphatase and ATPase. Furthermore, since the alkaline phosphatase appears to be restricted to the tegument (Cesari 1974, Wheater & Wilson 1976, the similar enrichment of this enzyme and the ATPase suggests that there is indeed little contamination of the isolated tegumental membranes with plasma membranes from other sources. Electron microscopical examination of the membrane fractions revealed a few large membranous sheets and numerous vesicles and membranous whorls (Figure 2)(c.f.…”
Section: Butterworth Et Almentioning
confidence: 94%
“…A major problem in such experiments was the lack of a defined intrinsic membrane marker. Previous reports (Cesari 1974, Wheater & Wilson 1976) had suggested that alkaline phosphatase was associated with the tegument, but its exact location was not known. Therefore, we relied initially on the recovery of surface-bound ('''l)-labeled wheat germ agglutinin (WGA) in order to identify tegumental membranes in various subcellular fractions of disrupted schistosomula, according to the techniques of Chang et al (1975).…”
Section: Butterworth Et Almentioning
confidence: 97%
“…Previous data on the presence of CaZ+-ATPase activity in S. mansoni consist of reports on the presence of ATPases activated by high concentrations of Ca 2+ or Mg 2+ [2][3][4][5] and of histochemical observations revealing ATPase activity in the tegument [14,15]. These ATPase activities referred to basic ATPases are probably not coupled to Ca 2+ transport.…”
Section: Discussionmentioning
confidence: 99%
“…A body cavity osmolarity higher than that of the environment attracts water that leaks through the tissues exposed to the environment, especially cuticle (Perry 1977;Wharton et al 1988;Bird and Zuckerman 1989) and intestinal cells (Stephenson 1942;Wright and Newall 1976), so the animal must eliminate excess water to maintain homeostasis.…”
Section: Osmoregulatory Function Of the Excretory Systemmentioning
confidence: 99%